(untitled) (Acta Scientiarum. Health Sciences, 2012)
The presence of ants in hospitals is a threat to the health of the hospital community, given the potential to carry pathogenic microorganisms. This study was developed in order to comment on publications related to the occurrence of ants associated with pathogenic microorganisms in hospitals in Brazil. Studies indicated that ants were collected in several wards of 13 hospitals in five States from South and Southeast regions. The microbiological analysis has identified on the ants, microorganisms such as Staphylococcus, Streptococcus, Klebsiella, Escherichia coli, Pseudomonas, and others with microbiological importance.